Chemical Quality of Chicken Sausage with The Addition of Bovine Bone Gelatin As a Binding Agent - Andi Nurul Mukhlisah; Setiawan Putra Syah; Weny Dwi Ningtiyas; Muhammad Irfan; Resa Vietna (Jurnal Penelitian Pendidikan IPA, 2024)
Sausage is a form of processed meat with the addition of seasonings, binders and other ingredients that are inserted into the sleeve. One of the binders that can be used in making sausages is gelatin, because it has high nutrition, gelling and stabilising emulsions. The purpose of this study was to determine the chemical quality of chicken sausages made with the addition of gelatin from beef bones. In addition, it can be information for the meat processing industry as a chelifier for processed meat. This research method used thigh bone (os femuris) for gelatin production. The experimental design used was a completely randomised design with a unidirectional pattern consisting of 5 treatments without the addition of 0% gelatine, 3% gelatine, 6% gelatine, 9% gelatine and 12% gelatine and 4 replicates with a total of 20 samples. The variables observed were chemical quality such as protein content, carbohydrate content, moisture content, ash content and fat content. The results showed that the protein content of sausages ranged from 14.13%-20.75%; carbohydrate content of sausages ranged from 4.75%-9.07%, fat content ranged from 0.50%-1.10%. Ash content ranged from 1.33% - 1.72%. And moisture content ranged from 68.23% - 76.02%. The best results were found in treatment P4 (12% cow bone gelatin). The use of gelatin up to 12% can be used as a binder in making chicken sausage.